“Knowing nothing about EDI:” A collaborative autoethnography exploring how an anti-racist project was created, publicized, and silenced - Pohl, Ethan; Ajadi, Tari; Soucy, Theo; Carroll, Heather; Earl, Jason; Verduyn, Christl; Connolly, Maureen (International Journal for Students as Partners, 2022)
This collaborative autoethnography explores how a group of students and professors from across Canada came together following racial justice protests of 2020. Driven by a desire to pressure Canadian higher education organizations to act on statements and commitments they had made regarding anti-racism, the group embraces a students-as-partners framework in the creation of a list of demands for institutions. Despite claims by such organizations that they were addressing racism, the demands were largely ignored. The authors explore both phases of the project, from factors leading to the successful creation of the demands to experiencing dismissal by the institutions they were designed to help. Twin messages are drawn from this work: students-as-partners is a powerful and useful method for engaging in conversations and taking action regarding anti-racism in higher education, yet this has little bearing on the institutions and structures which participate in oppression.